Dakwah Multikultural (Metode Dakwah Nabi Muhammad Kepada Non Muslim) - Mustoto (Mau'idhoh Hasanah, 2019)
Abstract This paper explains the Prophet's methods in conveying Islamic values to other religious communities: musyrik (polytheist) dan Ahli Kitab (Jews and Christian) in Mecca and Madinah phases. Qur'anic verses as well as tafsir will be resources and also other literatures on Prophet history. Some methods applied by Prophet to convey Islamic values to other religious community are: (1) dialogue method; (2) historical method; and (3) analogical method. The implementation of the methods is based on moral values in introducing Islam in the context of multicultural society throughout prophetical period, Mecca and Madina. So, every da'i Islam should make the principles as a guide in the contemporary Muslim life.